Follow-up criteria and cystoscopic classifications of bladder lesions: A retrospective analysis - Gurbuz, Recai; Salvarci, Ahmet (Annals of Medical Research, 2021)
Aim: To screen cystoscopically bladder cancer mimicking lesions and to present its clinical importance.Material and Methods: After receiving anamnesis of patients, hematological, biochemical, microbiological, cytological, pathologic and radiological assessments were performed. Randomized cold cup bladder biopsy, transurethral resection or open surgical excision were performed. The lesions were classified according to their cystoscopy appearance. Practical approach criterias were compiled based on their treatments and follow-up, throughout 9 years. Results: A total of 297 patients were reached .The mean age of all were 62±6 years. Almost all bladder lesions (95 %) were pre-diagnosed as bladder cancer according to the radiologic screening results like bladder wall thickening and irregularities. The precancerous /cancerous lesions were detected incidentally at a rate of 3.36 %. PAP (Papanicolaou) III urine cytology was observed at a rate of 3.4 %. Carcinoma in situ developed in the follow-ups and one converted to Grade I transitional cell cancer. Total cystectomy was required in a patient who was diagnosed with urinary tuberculosis.Conclusions: There may be precancerous or cancerous lesions in the background of these lesions which do not respond to treatment or constantly recur. There may be changes in favor of malignancies in lesions. The study created a different perspective on these lesions with cystoscopy classification.